METHANE EMISSIONS AND RICE YIELD IN RAINFED BED SYSTEM (SURJAN) AS AFFECTED BY MANURE AND ZEOLITE TREATMENT - Hervani, Anggri; Susilawati, Helena Lina; Wihardjaka, Anicetus (Universitas Muhammadiyah Yogyakarta, 2019)
Rainfed area as one of rice production areas is facing drought due to climate change. Management of rainfed area is needed due to its contribution, in addition to the production of rice, in producing methane as a contributor to greenhouse gas emission. This research aimed to investigate the methane emission status and yield from rainfed rice system with manure and zeolite treatment on the bed system (surjan). The doses of manure were 5, 15 and 30 tons/ha and the zeolite was 1 and 2.5 tons/ha. The result showed that all treatment had no significant effect on daily methane fluxe and grain yield in surjan system. However, the combination of manure at 15 tons/ha with zeolite at 1 ton/ha promoted higher methane emissions (63.43 kg CH4/ha/season). In addition, the combination treatment of manure at 5 tons/ha with zeolite at 2.5 tons/ha contributed to obtain higher grain yield (6.9 tons/ha).